Geographic variation in cranial shape in the Pumpkin Toadlet (Brachycephalus ephippium): A geometric analysis - Clemente-Carvalho, R. B. G.; Monteiro, L. R.; Bonato, V.; Rocha, H. S.; Pereira, G. R.; Oliveira, D. F.; Lopes, R. T.; Haddad, Celio Fernando Baptista [UNESP]; Martins, E. G.; dos Reis, S. F. (Soc Study Amphibians Reptiles, 2008)
The description of patterns of variation in any character system within well-defined species is fundamental for understanding lineage diversification and the identification of geographic units that represent opportunities for sustained evolutionary divergence. In this paper, we analyze intraspecific variation in cranial shape in the Pumpkin Toadlet, Brachycephalus ephippium-a miniaturized species composed of isolated populations on the slopes of the mountain ranges of southeastern Brazil. Shape variables were derived using geometric-statistical methods that describe shape change as localized deformations in a spatial framework defined by anatomical landmarks in the cranium of B. ephippium. By statistically weighting differences between landmarks that are not close together (changes at larger geometric scale), cranial variation among geographic samples of B. ephippium appears continuous with no obvious gaps. This pattern of variation is caused by a confounding effect between within-sample allometry and among-sample shape differences. In contrast, by statistically weighting differences between landmarks that are at close spacing (changes at smaller geometric scale), differences in shape within- and among-sample variation are not confounded, and a marked geographic differentiation among population samples of B. ephippium emerges. The observed pattern of geographic differentiation in cranial shape apparently cannot be explained as isolation-by-distance. This study provides the first evidence that the detection of morphological variation or lack thereof, that is, morphological conservatism, may be conditional on the scale of measurement of variation in shape within the methodological formalism of geometric morphometrics.